2021
DOI: 10.1111/1440-1681.13504
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0093887 upregulates CCND2 and SUCNR1 to inhibit the ox‐LDL‐induced endothelial dysfunction in atherosclerosis by functioning as a miR‐876‐3p sponge

Abstract: Circular RNAs (circRNAs) are widely expressed in mammals and act as regulatory targets in the atherogenesis. The objective of this study was to research the biological role and molecular mechanism of circ_0093887 in oxidized low‐density lipoprotein (ox‐LDL)‐induced atherosclerosis (AS) of human aortic endothelial cells (HAECs). Cell viability detection was performed by CCK‐8 assay. Inflammatory molecules were examined using ELISA. Flow cytometry was used to measure cell‐cycle progression and cell apoptotic rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…Circ-0044073 was involved in the development of AS via the sponge effect on miR-107 [ 19 ]. Circ_0093887 prevented the dysfunction of endothelial cells by binding to miR-876-3p [ 20 ]. Also, our data showed that circ_0002194 regulated ox-LDL-induced cell injury by serving as the miR-637 sponge.…”
Section: Discussionmentioning
confidence: 99%
“…Circ-0044073 was involved in the development of AS via the sponge effect on miR-107 [ 19 ]. Circ_0093887 prevented the dysfunction of endothelial cells by binding to miR-876-3p [ 20 ]. Also, our data showed that circ_0002194 regulated ox-LDL-induced cell injury by serving as the miR-637 sponge.…”
Section: Discussionmentioning
confidence: 99%
“…The spongy role between miRNAs and circRNAs had been demonstrated [30,31], for instance, circ_0093887 sponged miR-876-3p and miR-876 to protect human aortic endothelial cells (HAECs) from ox-LDL-induced damage [32]; Silencing circ_GRN acted as a sponge of miR-214-3p to abolish migration, proliferation, and inflammation of ox-LDL-exposed VSMCs [33]. In our study, we found that circ_0004104 sponged miR-942-5p in atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 For instance, circ_0093887 is reported to suppress ox-LDL-mediated dysfunction in ECs by sponging miR-876-3p. 30 Zhang et al 31 demonstrated that circ_0004104 silencing attenuates ox-LDL-mediated endothelial dysfunction by mediating miR-328-3p/TRIM14 signaling. Wang et al 32 found that circ_0124644 aggravates ox-LDL-induced injury in HUVECs by up-regulating PAPP-A via sponging miR-149-5p.…”
Section: Discussionmentioning
confidence: 99%